Trabalhar no fio da navalha : desafios de conciliar urgência e referência em saúde mental em tempos de precarização do trabalho e desmonte da reforma psiquiátrica brasileira - Daniela Tonizza de Almeida (2019)
In a sociopolitical and economic context characterized by the resurgence of authoritarian and conservative forces that are articulated to a neoliberal politics and precariousness of work, the historical achievements of guaranteeing the social rights of users and workers in the field of mental health are threatened. The purpose of this study was to investigate, from this context, what affects circulate, are produced and mobilized in work situations and how they are interrelated with the knowledge and values that guide the activities of the Higher Health Technicians in a Psychosocial Care Center. Above all, to understand how affections interfere in the relationships between the different subjects involved in the clinical processes and in their potential to act. In order to do so, it used Ergology as a dialogical and dialectical device that allowed to interweave theoretical knowledge and experience, combining a series of methodological strategies: bibliographical and documentary revision, field diaries, implication analysis, dialogues on the shared experience with fifteen workers. The dialogue with Psicossociology enabled the elucidation of elements that generate anguish and disengagement at work, as well as affections that had repercussions in the collapse of the collective at a time of institutional crisis. The precariousness of work has contributed to the erosion of the bonds that unite the collective and the impoverishment of the experience, causing a loss in the quality of work and the health of workers. Through the construction of images and metaphors that translated the affections and effects of the activity on the body, it was possible to verify that, faced with losses, privations and normative contradictions, the body appeared in the speeches as a mutilated image, "without legs" and front violence, as the "bulkhead" or "container" that contains it. However, the reference activity showed that the body is also loop and weaves network. The malaise in work appeared associated to a conjunction of social, historical and political aspects that converge and mix with the personal history of each subject, their desires and limits to produce a response to this malaise, supported by the values that sustain the struggles of each one with the real that affects him.